The effect of prescription patterns on the performance of the pharmacy department of a Regional Referral Hospital, Uganda - Gerald Manzi Mbabazize; Vedaste Kagisha; Kato J. Njunwa; Joseph Oloro (Taylor & Francis Group, 2024)
ABSTRACTBackground: Poor drug prescription patterns (PP) result in irrational medicine use, avoidable stock outs and drug expiries.Objective: This study primarily assessed the effects of PP on the performance of the pharmacy department (PD) of Mbarara Regional Referral Hospital (MRRH) Uganda.Methods: This was a mixed method cross-sectional study conducted in the outpatient department (OPD) of MRRH, questionnaires were administered to 86 prescribers and 300 patient prescriptions were reviewed. Ethical clearance was granted and informed consent of patients. Data were analysed, presented in the form of graphs, tables.Results: The overall prescription fill rate was 60.5%, being higher among dental officers and lower among those who did not adhere to generic prescribing and EML. Medical officers made most prescriptions at 69.3%. Prescriptions with four (47.1%) and six (17.5%) medicines respectively were made by clinical officers. Of the 300 prescriptions, 76% adhered to the Essential Medicines List (EML), 62% used generic name including 87.3% from dental officers and 52.9% by clinical officersThe overall prescription fill rate was 60.5%, being higher among dental officers and lower among those who did not adhere to generic prescribing and EML. Medical officers made most prescriptions at 69.3%. Prescriptions with four (47.1%) and six (17.5%) medicines respectively were made by clinical officers. Of the 300 prescriptions, 76% adhered to the Essential Medicines List (EML), 62% used generic name including 87.3% from dental officers and 52.9% by clinical officers.Conclusion: Prescription pattern affected the performance of the PD of MRRH, calling for its continued monitoring to ensure that guidelines are upheld, EML and UCG are availed and utilized.